Shortcake cake. 1 - Louie-Nishikawa, Emi (Shojo beat manga., 2018)
An unflappable girl and a cast of lovable male roommates at a boardinghouse create bonds of friendship and romance. When Ten moves out of her parents<U+2019> home in the mountains to live in a boardinghouse, she finds herself becoming fast friends with her male roommates. But can love and romance be far behind? Ten Serizawa has a two-hour commute through the mountains to high school every day, so she can<U+2019>t spend much time hanging out with her friends in the afternoon. She decides to move into the local boardinghouse, where one of her friends and three other boys are living. Ten<U+2019>s friends consider her to be as oblivious as a rock when it comes to noticing boys and falling in love, but will she be able to keep her calm and steady heart in her new living situation?